2023
DOI: 10.1073/pnas.2311913120
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α 5 β 1 contributes to cell fusion and inflammation mediated by SARS-CoV-2 spike via RGD-independent interaction

Heng Zhang,
Zhengli Wang,
Huong T. T. Nguyen
et al.

Abstract: The Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus infects host cells by engaging its spike (S) protein with human ACE2 receptor. Recent studies suggest the involvement of integrins in SARS-CoV-2 infection through interaction with the S protein, but the underlying mechanism is not well understood. This study investigated the role of integrin α 5 β 1 , which recognizes the Arg-Gly-Asp (RGD) motif in its physiological ligands, in S-mediated viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…This interaction has the potential to affect cellular adhesion and signaling cascades. In addition, it was demonstrated that alpha integrin α5β1 plays a crucial role in facilitating the fusion of cells and triggering inflammatory responses [ 52 ]. Also, in silico identified, Syndecan-4, prevalent in the lungs, promotes the transmission of the Delta variant of SARS-CoV-2 by binding to its altered spike glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction has the potential to affect cellular adhesion and signaling cascades. In addition, it was demonstrated that alpha integrin α5β1 plays a crucial role in facilitating the fusion of cells and triggering inflammatory responses [ 52 ]. Also, in silico identified, Syndecan-4, prevalent in the lungs, promotes the transmission of the Delta variant of SARS-CoV-2 by binding to its altered spike glycoprotein.…”
Section: Discussionmentioning
confidence: 99%